Theoretical and methodological approach to forming a digital transformation strategy for enterprises in the investment and construction sphere - Leshchinsky, V. (Ways to Improve Construction Efficiency, 2022)
This study aims to investigate and evaluate the main components of the theoretical and methodological approach to the formation of various types of strategies that are based on the digital economy and allow the use of information technologies. To consider the main theoretical approaches to justifying and determining the need to take into account digitalization by enterprises in the investment and construction sector. Taking into account the specific characteristics of the activities of investment and construction enterprises, optimal methods and an algorithm for developing a digitalization strategy for investment and construction enterprises are proposed. The recommended structure of the digital transformation strategy is considered and the functional blocks identified by the author as a result of its analysis are universal in nature and can be used by any organization or enterprise in both the public and private sectors of the economy, regardless of industry affiliation. However, the specifics of a particular industry may impose some features on the process and content of the digital transformation strategy, taking into account such industry features will increase the practical significance of approaches, methods and tools for its formation. Based on the above, the author has formed a methodological approach to the formation of a digital transformation strategy for enterprises in the investment and construction sector.